Evaluation of coupling coordination degree between urban rail transit and land use. (28th May 2019) - Liu, Weiwei; Wang, Jin
Summary: In order to analyze rail transit‐land use system from multiple angles and aspects, this paper proposed a new evaluation index system, which can assess the extent of coordination between urban rail transit and land use. First, the index system which reflected the developmental level of urban rail transit and land use system was structured by system theory. Then, according to efficacy function, the comprehensive development level of rail transit system and land use system was calculated, thus constructing the coupling coordination degree model. And quantitative analyses of the coordination of rail transit‐land use system in Shanghai city were conducted through comprehensive development index and coupling coordination degree proceeding from time series. It was found that the integrated developmental level of urban rail transit system and land use system in Shanghai city rose steadily, and the coupling interaction effect of two systems was obvious. Meanwhile, the sequential change presents different phases and undulations. In 2000 to 2004, the synergistic effect of rail transit system and land use system was weak as the disorder stage. In 2005 to 2006, the synergistic effect began to appear. In 2007 to 2010, the interactive effect increased as the coordination stage, but the overall coupling coordination grade was still low. The conclusion indicated that it is also necessary to reasonably increase the level of rail transit construction and land use development to promote the harmonious development of Shanghai rail transit and land use system from primary coordination to good quality. Abstract : In order to deeply study the coordinated development and interaction effect between rail transit and land use system, this paper regards rail transit and land use as one subsystem, respectively, which are coupled into one large system. A comprehensive evaluation index system and coupling coordination degree model were established to evaluate coordinated development of rail transit and land use for 10 levels.